2011
DOI: 10.1007/s10096-011-1166-5
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C and B prevalence in Spanish prisons

Abstract: Purpose: The Prevalhep study seeks to determine the prevalence of factors associated with hepatitis C virus (HCV) and B (HBV) in Spanish prisoners Methods: Observational, cross-sectional study which randomly selected 18 Spanish prisons to participate, and with 21 prisoners/CentreResults: There were 378 prisoners selected, 370 of whom had serological HCV and 342 had VHB data. The HCV population were predominantly male (91.6%), of middle age (66.7% contact status with HBV (HBcAb+ and/or HBsAg+), while 37.5% were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 25 publications
5
30
2
1
Order By: Relevance
“…Compared to Italian, foreign prisoners showed a lower prevalence of HCV infection, with African born patients, among foreigners, demonstrating the highest one, as published elsewhere [2]. Not surprisingly, women had a higher prevalence of HCV infection than men, as higher rates of Hepatitis B and C, HIV, and sexually transmitted infection, estimated at 2–10 times that of the general population were observed among imprisoned women, moreover, women had a significantly higher prevalence of all medical and psychiatric conditions and drug dependence when compared with imprisoned men [16].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Compared to Italian, foreign prisoners showed a lower prevalence of HCV infection, with African born patients, among foreigners, demonstrating the highest one, as published elsewhere [2]. Not surprisingly, women had a higher prevalence of HCV infection than men, as higher rates of Hepatitis B and C, HIV, and sexually transmitted infection, estimated at 2–10 times that of the general population were observed among imprisoned women, moreover, women had a significantly higher prevalence of all medical and psychiatric conditions and drug dependence when compared with imprisoned men [16].…”
Section: Discussionsupporting
confidence: 63%
“…HCV infection in prison inmates is widespread, surveys in correctional system show an HCV sero-prevalence ranging from 16% to 42% in U.S.A. [1], 30% to 50% in European Countries [2] and 31% to 38% among Italian inmates [3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…We added the number of infectious diseases known at the moment of relapse in order to examine the possible effect of multiple comorbid conditions. Previous research has shown important differences in levels of risk by number of comorbid infections in similar populations (Pallas et al, 1999; Ramezani et al, 2014; Saiz de la Hoya et al, 2011)…”
Section: Methodsmentioning
confidence: 99%
“…In Spain, 1.6–2.6% of the population is infected with HCV, with disproportional representation from prisoners and the IDU population [6]. The presence of HCV infection among prisoners reached 48% in 1998 [7] and 22% in 2010 [8]. Changes in HCV prevalence in the general population and in the characteristics of the inmate population, such as a lower percentage of IDU, are responsible of the reduced incidence of HCV infection in prisons in recent years.…”
Section: Introductionmentioning
confidence: 99%